KETIKA MEMBUNUH MENJADI SEBUAH PENYELESAIAN: SEBUAH TINJAUAN FENOMENOLOGIS MENGENAI TINDAKAN SESEORANG MELAKUKAN PEMBUNUHAN - Agus Wahyudi (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2017)
Murder is an evil action to take the soul of others. Everyone can be a murderer. Sociocultural background such as: age, sex, socio-economic, ethnic, and religion is not the reason for someone to kill others. Many factors make someone decide to kill others. One of the factors is known as killing motive. This qualitative research used the primary data. The subject were 5 people. There were 4 motives to kill, they are polygamy, money, debt, and frustration.